Effect of Postnatal Epigallocatechin-Gallate Treatment on Cardiac Function in Mice Prenatally Exposed to Alcohol - Vicente Andreu-Fernández; Mariona Serra-Delgado; Laura Almeida-Toledano; Àgueda García-Meseguer; Melina Vieiros; Anna Ramos-Triguero; Concha Muñoz-Lozano; Elisabet Navarro-Tapia; Leopoldo Martínez; Óscar García-Algar; María D. Gómez-Roig (MDPI AG, 2023)
Prenatal alcohol exposure affects the cardiovascular health of the offspring. Epigallocatechin-3-gallate (EGCG) may be a protective agent against it, but no data are available regarding its impact on cardiac dysfunction. We investigated the presence of cardiac alterations in mice prenatally exposed to alcohol and the effect of postnatal EGCG treatment on cardiac function and related biochemical pathways. C57BL/6J pregnant mice received 1.5 g/kg/day (Mediterranean pattern), 4.5 g/kg/day (binge pattern) of ethanol, or maltodextrin until Day 19 of pregnancy. Post-delivery, treatment groups received EGCG-supplemented water. At post-natal Day 60, functional echocardiographies were performed. Heart biomarkers of apoptosis, oxidative stress, and cardiac damage were analyzed by Western blot. BNP and Hif1α increased and Nrf2 decreased in mice prenatally exposed to the Mediterranean alcohol pattern. Bcl-2 was downregulated in the binge PAE drinking pattern. Troponin I, glutathione peroxidase, and Bax increased in both ethanol exposure patterns. Prenatal alcohol exposure led to cardiac dysfunction in exposed mice, evidenced by a reduced ejection fraction, left ventricle posterior wall thickness at diastole, and Tei index. EGCG postnatal therapy restored the physiological levels of these biomarkers and improved cardiac dysfunction. These findings suggest that postnatal EGCG treatment attenuates the cardiac damage caused by prenatal alcohol exposure in the offspring.